PENERAPAN MODEL PBL BERBANTUAN FLASH CARD UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA KELAS IV SD - Delia Novita; Yuni Ratnasari; Lintang Kironoratri (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2024)
The process of learning Indonesian, which still relies on printed textbooks, conventional learning models, and does not use varied learning media, makes learning Indonesian at the elementary school level seem boring and students are less active. This is the basis for research to apply the PBL model with the help of Flash Cards in Indonesian language learning. This research aims to find out how the application of the PBL model assisted by Flash Cards can increase the learning activities of fourth grade elementary school students on the material of writing simple procedural texts. The hypothesis of this research is that the application of the PBL model with the help of Flash Cards can increase the learning activities of fourth grade elementary school students. The type of research is PTK which will be carried out in class IV of SDN 4 Besito with 24 students as research subjects. This research lasted two cycles, each cycle consisting of four stages, namely the planning, implementation, observation and reflection stages. The research results showed an increase in student learning activities from the first cycle, which was initially 60.5%, increasing to 83.5% in the second cycle. Based on these results, this research hypothesis is proven.